Superior Performance of Silver Bismuth Iodide Photovoltaics Fabricated via Dynamic Hot‐Casting Method under Ambient Conditions. Issue 33 (14th October 2018) - Ghosh, Biplab; Wu, Bo; Guo, Xintong; Harikesh, Padinhare Cholakkal; John, Rohit Abraham; Baikie, Tom; Arramel,; Wee, Andrew T. S.; Guet, Claude; Sum, Tze Chien; Mhaisalkar, Subodh; Mathews, Nripan
Abstract: Bismuth‐based ternary halides have recently gained a lot of attention as lead‐free perovskite materials. However, photovoltaic performances of these devices remain poor, mostly due to their low‐dimensional crystal structure and large bandgap. Here, a dynamic hot casting technique to fabricate silver bismuth iodide‐based perovskite solar cells under an ambient atmosphere with power conversion efficiencies above 2.5% is demonstrated. Silver bismuth iodides are 3D analogs of complex ternary bismuth halides with a suitable bandgap for a single junction solar cell. As far as it is known, these results represent the highest efficiency for solution processed air‐stable lead‐free perovskite solar cells. The enhanced solar cell performance via this dynamic hot casting technique can be attributed to long carrier lifetimes, micrometer‐sized crystalline grains, and pinhole free thin‐film formation with uniform morphology. This work provides a new direction for fabrication of solution‐processed lead‐free perovskite solar cells with a rapid fabrication strategy irrespective of the processing environment. Abstract : A dynamic hot casting technique is presented to fabricate silver bismuth iodide‐based perovskite solar cells under an ambient atmosphere with power conversion efficiencies above 2.5%. The enhanced solar cell performance can be ascribed to pin‐hole free thin‐film formation with uniform morphology, micrometer‐sized crystalline grains, and long carrier lifetime.